ANALISIS DAN PERANCANGAN SPK PEMILIHAN PNS TELADAN DENGAN METODE SAW PADA BKD PROVINSI JAMBI - Karsa, Sigit Eka; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2017)
Regional Personnel Agency (BKD) the Jambi provincial government is an organization that handles affairs - affairs staffing environment Jambi provincial government, one election silyl exemplary public servant. For example the selection of civil servants still use the registry system manually. Then investigated and corrected if these employees deserve to be exemplary civil servants. After that didapatlah list of names - names of employees eligible. Then sealed by officials echelon existing at BKD Jambi provincial government. So the authors designed a system that can assist and facilitate the leadership in making decisions in the selection of civil servants exemplary. To help the decision-making system using fuzzy logic decisions. The results of this system design can facilitate BKD Head of Jambi province, and also can shorten the time civil servants exemplary election.